The effect of impingement angle on erosion wear characteristics of HVOF sprayed WC-Ni and WC-Cr3C2-Ni cermet composite coatings - Yirui Chen; Yuping Wu; Sheng Hong; Weiyang Long; Xiulin Ji (Materials Research Express, 2020)
The present study investigated the erosion wear behavior of WC-Ni and WC-Cr _3 C _2 -Ni cermet coatings deposited by high velocity oxy-fuel (HVOF) spray process on the substrate of 1Cr18Ni9Ti stainless steel. Microstructures and morphologies of the coatings were examined using SEM images, and x-ray diffractometer was used to analyze the phase composition of the powder and the coatings. The erosion test was carried out using home-made jet rig. In order to better fit the research background of this study, the erodent used for erosion was taken from the Yellow River, China. The coating is well combined with the substrate; and WC-Cr _3 C _2 -Ni coating consists of WC, Cr _3 C _2 and Ni phases, WC-Ni coating consists of WC, W _2 C and Ni phases. Some mechanical properties of the two coatings were compared, WC-Cr _3 C _2 -Ni coatings have higher hardness to be compared with WC-Ni ones due to a lower binder content; and the elasticity modulus and nano-hardness values of the WC-Cr _3 C _2 -Ni coating are higher than that of the WC-Ni coating. The relationship between the wear performance of the coatings and impingement angle was obtained; and the erosion resistance of the coatings was analyzed. It was observed that WC-Cr _3 C _2 -Ni cermet coating exhibits higher erosion resistance under all testing conditions as compared with the WC-Ni cermet coating and 1Cr18Ni9Ti stainless steel. The results show that the erosion mechanism at low angle is mainly cutting, while erosion pits dominate at high angle for the coatings, moreover, plastic deformation could be observed in the case of the binder depletion and cracking found place. and the erosion mechanisms of the 1Cr18Ni9Ti stainless steel are mainly cutting and plastic deformation at low angle and high angle, respectively.